High frequency ultrasound for the diagnosis of skin cancer in adults - Dinnes, Jacqueline; Bamber, Jeffrey; Chuchu, Naomi; Bayliss, Susan E.; Takwoingi, Yemisi; Davenport, Clare; Godfrey, Kathie; O'Sullivan, Colette; Matin, Rubeta N.; Deeks, Jonathan J.; Williams, Hywel C. (Wiley, 2018)
Background: Early accurate detection of all skin cancer types is essential to guide appropriate management and to improve morbidity and survival. Melanoma and squamous cell carcinoma (SCC) are high risk skin cancers which have the potential to metastasise and ultimately lead to death, whereas basal cell carcinoma (BCC) is usually localised with potential to infiltrate and damage surrounding tissue. Anxiety around missing early curable cases needs to be balanced against inappropriate referral and unnecessary excision of benign lesions. Ultrasound is a non-invasive imaging technique which relies on the measurement of sound wave reflections from the tissues of the body. At lower frequencies, the deeper structures of the body such as the internal organs can be visualised, while high frequency ultrasound (HFUS) with transducer frequencies of at least 20MHz, has a much lower depth of tissue penetration but produces a higher resolution image of tissues and structures closer to the skin surface. Used in conjunction with clinical or dermoscopic examination of suspected skin cancer, or both, HFUS may offer additional diagnostic information compared to other technologies. Objectives: To determine the diagnostic accuracy of HFUS to assist in the diagnosis of (a) melanoma and intraepidermal melanocytic variants, (b) cutaneous squamous cell carcinoma (cSCC), and (c) basal cell carcinoma (BCC) in adults. Search methods: We undertook a comprehensive search of the following databases from inception up to August 2016: Cochrane Central Register of Controlled Trials; MEDLINE; EMBASE; CINAHL; CPCI; Zetoc; Science Citation Index; US National Institutes of Health Ongoing Trials Register; NIHR Clinical Research Network Portfolio Database; and the World Health Organization International Clinical Trials Registry Platform. We studied reference lists and published systematic review articles. Selection criteria: Studies evaluating HFUS (>= 20 MHz) in adults with lesions suspicious for melanoma, cSCC or BCC, compared with a reference standard of histological confirmation or clinical follow-up. Data collection and analysis: Two review authors independently extracted all data using a standardised data extraction and quality assessment form (based on QUADAS-2). Due to scarcity of data and poor quality of studies, no meta-analysis was undertaken for this review. For illustrative purposes, estimates of sensitivity and specificity were plotted on coupled forest plots. Main results: Six studies were included, providing 29 datasets, 20 for diagnosis of melanoma (1125 lesions and 242 melanomas) and 9 for diagnosis of BCC (993 lesions and 119 BCCs). No data relating to the diagnosis of cSCC were identified. Studies were generally poorly reported limiting judgements of methodological quality. Half of studies did not set out to establish test accuracy and all should be considered preliminary evaluations of the potential usefulness of HFUS. There were particularly high concerns for applicability of findings due to selective study populations and data driven thresholds for test positivity. Studies reporting qualitative assessments of HFUS images excluded up to 22% of lesions (including some melanomas) due to them not being visualised by the test. Derived sensitivities for qualitative HFUS characteristics were at least 83% (95% CI 75% to 90%) for the detection of melanoma; the combination of three features (lesions appearing hypoechoic, homogenous and well defined) demonstrating 100% sensitivity in two studies, with variable corresponding specificities of 33% (95% CI 20% to 48%) and 73% (95% CI 57% to 85%) (Lower limits of the 95% CIs for sensitivities were 94% and 82% respectively). Quantitative measurement of HFUS outputs in two studies enabled decision thresholds to be set to achieve 100% sensitivity; specificities were 93% (95% CI 77% to 99%) and 65% (95% CI 51% to 76%). It was not possible to make summary statements regarding HFUS accuracy for the diagnosis of BCC due to highly variable sensitivities and specificities. Authors' conclusions: Insufficient data are available on the potential value of HFUS in the diagnosis of melanoma or BCC. Given the between study heterogeneity, unclear to low methodological quality and limited volume of evidence, no implications for practice can be drawn. The main value of the preliminary studies included may be in provision of guidance on the possible components of future diagnostic rules for diagnosis of melanoma or BCC using HFUS that require future evaluation. A prospective evaluation of HFUS added to visual inspection and dermoscopy alone in a standard health care setting with a clearly defined and representative population of participants would be required for a full and proper evaluation of accuracy.